Decision to enroll in post-graduate education: What are the predictors? - Bakar, Ab. Rahim; Mohamed, Shamsiah; Mat Rashid, Abdullah (The International Journal of Interdisciplinary Social Sciences, 2009)
The objective of the study was to predict students’ decision to enroll for a doctoral program at the Faculty of Educational Studies. A discriminant analysis was conducted to investigate the predictors that influence a student’s decision to enroll for a doctoral program. The predictors investigated were job factors, personal factors, program factors, social factors, satisfaction, and academic performance. The overall Wilk’s Lambda was significant, Λ = 0.87, Chi-Square (6, n = 117) = 15.99, p = 0.014. This indicated that the predictors were significantly different among groups of student who plan to enroll for a doctoral program (Group 1) and those who do not (Group 2). Of the total 117 students, 90 (76%) were classified correctly.